Improving Operational Performance: The Influence of Buyer-Supplier Relationship, Supply Chain Quality, and Firm CSR to Enhancing Supplier Performance - Ardhia Widiaswara; Wahyuningsih Santosa; Triwulandari Satitidjati Dewayana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the influence of the buyer-supplier relationship, supply chain quality, and corporate social responsibility on supplier performance, as well as how supplier performance influences operational performance. This study employs a Conclusive Design with a Cross-Sectional Design type. Data is collected through Multiple Cross-Sectional methods, where data is taken one time from one group of respondents in stages. A non-probability sampling technique was applied because not all members of the population could become samples. The results of the research indicate that there is a positive influence of the buyer-supplier relationship and corporate social responsibility on supplier performance. Additionally, there is a positive influence of the buyer-supplier relationship, corporate social responsibility, and supplier performance on operational performance. However, no positive influence of supply chain quality on supplier performance or operational performance was found.